Isolation Rearing Reduces Neuronal Excitability in Dentate Gyrus Granule Cells of Adolescent C57BL/6J Mice: Role of GABAergic Tonic Currents and Neurosteroids - Talani, Giuseppe; Biggio, Francesca; Licheri, Valentina; Locci, Valentina; Biggio, Giovanni; Sanna, Enrico (Frontiers in Cellular Neuroscience, 2016)
Early-life exposure to stress, by impacting on a brain still under development, is considered a critical factor for the increased vulnerability to psychiatric disorders and abuse of psychotropic substances during adulthood. As previously reported, rearing C57BL/6J weanling mice in social isolation (SI) from their peers for several weeks, a model of prolonged stress, is associated with a decreased plasma and brain levels of neuroactive steroids such as 3α,5α-THP, with a parallel up-regulation of extrasynaptic GABAA receptors (GABAAR) in dentate gyrus (DG) granule cells compared to group-housed (GH) mice. In the present study, together with the SI-induced decrease in plasma concentration of both progesterone and 3α,5α-THP, and an increase in THIP-stimulated GABAergic tonic currents, patch-clamp analysis of DG granule cells revealed a significant decrease in membrane input resistance and action potential (AP) firing rate, in SI compared to GH mice, suggesting that SI exerts an inhibitory action on neuronal excitability of these neurons. Voltage-clamp recordings of glutamatergic spontaneous excitatory postsynaptic currents (sEPSCs) revealed a SI-associated decrease in frequency as well as a shift from paired-pulse (PP) depression to PP facilitation (PPF) of evoked EPSCs, indicative of a reduced probability of glutamate release. Daily administration of progesterone during isolation reverted the changes in plasma 3α,5α-THP as well as in GABAergic tonic currents and neuronal excitability caused by SI, but it had only a limited effect on the changes in the probability of presynaptic glutamate release. Overall, the results obtained in this work, together with those previously published, indicate that exposure of mice to SI during adolescence reduces neuronal excitability of DG granule cells, an effect that may be linked to the increased GABAergic tonic currents as a consequence of the sustained decrease in plasma and hippocampal levels of neurosteroids. All these changes may be consistent with cognitive deficits observed in animals exposed to such type of prolonged stress.